2022
DOI: 10.1155/2022/6555883
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Vitamin D3 on the Alignment of Mandibular Anterior Teeth: A Randomized Controlled Clinical Trial

Abstract: Objectives. To investigate the effect of vitamin D3 level on the alignment of mandibular anterior teeth in adults and explore the associated root resorption and pain perception. Trial Design. Multicentre, double blinded randomized clinical trial. Subjects and Methods. Adult patients aged 18–30 years, with moderate mandibular incisor crowding [Little’s Irregularity index (LII) 3–6 mm], needing nonextraction treatment with fixed orthodontic appliance, were randomly allocated into two groups with 1 : 1 allocation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 52 publications
0
12
1
Order By: Relevance
“…However, the abovementioned results were contrary to that of Tehranchi et al (2017), who demonstrated no significant correlation between the VD serum level and external apical root resorption development (55) . Moreover, this result was inconsistent with that of Al-Attar and Abid (2022), who demonstrated a nonsignificant correlation between root resorption and VD serum level after the first three months of orthodontic treatment (13) . A different method of root resorption assessment could be used, as the latter used a periapical radiograph with a digital sensor as opposed to the gold standard for histological investigation in the current study.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…However, the abovementioned results were contrary to that of Tehranchi et al (2017), who demonstrated no significant correlation between the VD serum level and external apical root resorption development (55) . Moreover, this result was inconsistent with that of Al-Attar and Abid (2022), who demonstrated a nonsignificant correlation between root resorption and VD serum level after the first three months of orthodontic treatment (13) . A different method of root resorption assessment could be used, as the latter used a periapical radiograph with a digital sensor as opposed to the gold standard for histological investigation in the current study.…”
Section: Discussioncontrasting
confidence: 91%
“…A correlation was observed between root resorption and VD receptor gene polymorphism (12) . However, the relationship of VDD and root resorption was inconclusive, probably because of published data with short-term follow-up (13) .…”
Section: Introductionmentioning
confidence: 99%
“…After applying a linear regression model to control for the effect of confounders, they found no significant correlation between serum levels of vitamin D and EARR, which was in line with the present findings. In a recent study, Al-Attar and Abid [ 24 ] evaluated the serum level of vitamin D3 and detected no significant correlation between the serum level of vitamin D and root resorption due to orthodontic treatment. However, it should be noted that they only evaluated patients for a 3-month period at the onset of treatment during the leveling and alignment phase, and thus, their results cannot reflect the effect of the entire course of orthodontic treatment; whereas, the present study evaluated pre- and post-treatment radiographs of patients who underwent comprehensive orthodontic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Al-Attar et al study, 39 the sample size for this study was estimated and based on the ability to distinguish a clinically relevant difference in the orthodontic tooth (primary outcome) in the three groups of the trial, with a significance level of .05 and 80% power. Based on the calculation, at least 23 patients had to be assigned to each group.…”
Section: Methodsmentioning
confidence: 99%